Functions of determinological lexics in works of literature of Kherson region (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article on the material of works of literature of poets of Kherson region functions of determinological lexics are defined.
Keywords: lexical system; terminology; determilogical lexics; term